A dielectrophoresis method to manipulate and monitor the Shewanella oneidensis. Issue 2 (June 2016) - Chen, Xiangyu; Chen, Shan; Xiong, Ying; Xiong, Penghui; Hou, Shuangyue; Zhang, Xiaobo; Liu, Gang; Tian, Yangchao; Zheng, Jinjin
Shewanella oneidensis is capable of producing electrons and transferring to the solid electrodes. To characterize the electrical properties of S. oneidensis and manufacture the miniature microbial fuel cells, cellular dielectrophoresis has been developed into a powerful and flexible tool to utilize microfabricated electrode arrays fulfilling S. oneidensis manipulation and monitoring. When S. oneidensis with green fluorescent protein were placed under the influence of an applied inhomogeneous field, the translation and enrichment of the green bacteria were observed by the fluorescence microscope. The distribution of electric field around the microelectrodes was simulated in finite element analysis software. The dielectrophoresis manipulation parameters were also optimized according to the peak value of applied alternating current signals and its frequency. In short, this study shows that dielectrophoresis can be a valuable tool to manipulate S. oneidensis to the sidewalls of microelectrode.